Genetic improvement and related activities. Improvement of individual characters. Snap beans - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1987)
Snap bean improvement at CIAT has been carried out collaboratively with Washington State U. since 1983, to incorporate disease resistance and tropical adaptation from the dry bean improvement programs into green beans. An international adaptation nursery of advanced snap bean lines was distributed to 14 countries in Asia, Africa, Europe, and America. The current nursery consists of 204 bush and 32 climbing lines. In collaboration with the Instituto Colombiano Agropecuario, a regional trial of 19 and 14 bush and climbing snap bean lines, resp., was distributed. All climbing lines were resistant to anthracnose, the best being HAB 208, HAB 214, HAB 232, HAB 234, HAB 235, and HAB 236. Bush lines HAB 87, HAB 141, and HAB 173 were resistant to anthracnose, rust, and BCMV. (CIAT) El mejoramiento de habichuela en CIAT se ha realizado en colaboracion con la U. del estado de Washington desde 1983, para incorporar la resistencia a enfermedades y la adaptacion tropical de los programas de mejoramiento de frijol a la habichuela. Se distribuyo un vivero internacional de adaptacion de lineas avanzadas de habichuela a 14 paises en Asia, Africa, Europa y America. El vivero actual consta de 204 lineas arbustivas y 32 trepadoras. Se distribuyo un ensayo regional de 19 y 14 lineas de habichuela arbustivas y trepadoras, resp., en colaboracion con el Instituto Colombiano Agropecuario. Todas las lineas trepadoras eran resistentes a antracnosis, siendo HAB 208, HAB 214, HAB 232, HAB 234, HAB 235 y HAB 236 las mejores. Las lineas arbustivas HAB 87, HAB 141 y HAB 173 eran resistentes a antracnosis, roya y 013028 DEL 09 013028 ADD 09 Genetic improvement and related activities. Improvement of individual characters. Yield potential